2017
DOI: 10.1016/j.talanta.2017.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing and bio-imaging applications based on polyethylenimine/CaF2 nanoparticles with upconversion fluorescence

Abstract: Rare earth ion-doped upconversion nanoparticles (UCNPs) have become a research hotspot for their applications such as nano-thermometry and bio-imaging. Here we report one pot solvothermal synthesis of polyethylenimine (PEI) coated CaF: 1%Er, 2%Yb UCNPs with good water-solubility and biocompatibility. The nanoparticles show a spherical shape with an average size of 40nm and display intense green light (Yb and Er) under the 980nm irradiation. The maximum sensitivity of temperature sensing in the biological tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…CaF 2 is a nontoxic optical material with high solubility of REIs, low phonon energy, high chemical stability, and wide transmittance range, thus exhibiting great potential applications involving upconversion, optical waveguides, solar cells, biological windows, etc. Therefore, it is expected that CaF 2 can be used as a good alternative material for Pb x Cd (1– x ) F 2 and PbF 2 . Fu et al first reported Eu 2+ -doped transparent oxyfluoride glass ceramics containing CaF 2 nanocrystals where the Eu 2+ has higher luminescence than in the precursor glasses .…”
Section: Introductionmentioning
confidence: 99%
“…CaF 2 is a nontoxic optical material with high solubility of REIs, low phonon energy, high chemical stability, and wide transmittance range, thus exhibiting great potential applications involving upconversion, optical waveguides, solar cells, biological windows, etc. Therefore, it is expected that CaF 2 can be used as a good alternative material for Pb x Cd (1– x ) F 2 and PbF 2 . Fu et al first reported Eu 2+ -doped transparent oxyfluoride glass ceramics containing CaF 2 nanocrystals where the Eu 2+ has higher luminescence than in the precursor glasses .…”
Section: Introductionmentioning
confidence: 99%
“…Among temperature dependent optical performance, such as peak position (Jiang et al, 2014), luminescent lifetime (Peng et al, 2010), emission intensity (Zhou et al, 2016), and bandwidth (Walsh and Di Bartolo, 2015), fluorescence intensity ratio (FIR) technique (Liu et al, 2017; Xu et al, 2017) can achieve accurate temperature measurement, which is independent of external interferences, spectral losses, as well as fluctuations in the excitation density (Wade et al, 2003; Wawrzynczyk et al, 2012; Zhou et al, 2014; Pandey et al, 2015; Wang et al, 2015). Using this ratiometric technique, the sensitivity of sensor is strongly dependent on the energy gap of thermally coupled levels (TCL), which is confined in the range of 200–2,000 cm −1 (Zheng et al, 2016; Du et al, 2017; Tong et al, 2017; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the fluorescence intensity ratio ( FIR ) between two thermally coupled energy levels of trivalent rare earth ions is considered to be a promising technology to provide fast and accurate optical thermometry, due to its rapid response capability, high spatial resolution, strong anti‐jamming ability, etc 12‐17 . Up to date, numerous trivalent rare earth ions are used for ratiometric thermometry, such as Er 3+ , Ho 3+ , Tm 3+ , Nd 3+ , and Eu 3+ 18‐25 . Among these ions, Er 3+ is the most widely used activator for temperature sensing which has been realized in an enormous variety of materials, due to the excellent thermal coupling between the green emitting levels 2 H 11/2 and 4 S 3/2 of Er 3+ as well as their strong UC intensity under the excitation of 980 nm excitation with the sensitization of Yb 3+ 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Up to date, numerous trivalent rare earth ions are used for ratiometric thermometry, such as Er 3+ , Ho 3+ , Tm 3+ , Nd 3+ , and Eu 3+ . [18][19][20][21][22][23][24][25] Among these ions, Er 3+ is the most widely used activator for temperature sensing which has been realized in an enormous variety of materials, due to the excellent thermal coupling between the green emitting levels 2 H 11/2 and 4 S 3/2 of Er 3+ as well as their strong UC intensity under the excitation of 980 nm excitation with the sensitization of Yb 3+ . 26,27 Nevertheless, the thermometric sensitivity and resolution as well as the signal to noise ratio (SNR) of Er 3+typed optical thermometer are still need to be improved.…”
Section: Introductionmentioning
confidence: 99%